Pituitary adenylate cyclase‐activating polypeptide in the testis of the quail Coturnix coturnix: Expression, localization, and phylogenetic analysis. Issue 3 (21st February 2019) - Prisco, Marina; Rosati, Luigi; Agnese, Marisa; Aceto, Serena; Andreuccetti, Piero; Valiante, Salvatore
Abstract: To evaluate the involvement of pituitary adenylate cyclase‐activating polypeptide (PACAP)/receptors system in the control of testis activity, we have investigated the expression and localization of PACAP and the distribution of its receptors in the testis of mature samples of quail Coturnix coturnix, and we have performed a phylogenetic analysis of PACAP in birds. Using histological, molecular, and bioinformatics tools, we demonstrated that (a) PACAP messenger RNA shows a high sequence identity with that reported in other birds studied so far and in other vertebrates. Furthermore, we showed that purifying selection acts on PACAP; (b) the PACAP peptide is present only in Leydig cells, whereas its receptors are localized within both Leydig and germ cells; (c) the synthesis of PACAP does not take place in seminiferous tubules. The role of PACAP in the control of spermatogenesis and steroidogenesis in birds is discussed. Finally, we talk about the phylogenetic and evolutionary relationships between PACAP in birds and in other vertebrates.